2006
DOI: 10.1074/jbc.m605122200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Acid-sensing Ion Channel Currents, Acid-induced Increase of Intracellular Ca2+, and Acidosis-mediated Neuronal Injury by Intracellular pH

Abstract: Acid-sensing ion channels (ASICs), activated by lowering extracellular pH (pH o ), play an important role in normal synaptic transmission in brain and in the pathology of brain ischemia. Like pH o , intracellular pH (pH i ) changes dramatically in both physiological and pathological conditions. Although it is known that a drop in pH o activates the ASICs, it is not clear whether alterations of pH i have an effect on these channels. Here we demonstrate that the overall activities of ASICs, including channel act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 40 publications
5
74
0
Order By: Relevance
“…Most modulators of ASIC1a function, including zinc, redox reagents, lactate, and PcTx1, act by altering the apparent proton sensitivity of the channel (16,18,25,(31)(32)(33)(34). These compounds also impact ASIC1a-induced neuronal death (8,9,15,31). We find that two protein regions, located between amino acids 87 and 197 and between amino acids 323-431 of the extracellular domain are both necessary and sufficient for high affinity proton sensing of ASIC1a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most modulators of ASIC1a function, including zinc, redox reagents, lactate, and PcTx1, act by altering the apparent proton sensitivity of the channel (16,18,25,(31)(32)(33)(34). These compounds also impact ASIC1a-induced neuronal death (8,9,15,31). We find that two protein regions, located between amino acids 87 and 197 and between amino acids 323-431 of the extracellular domain are both necessary and sufficient for high affinity proton sensing of ASIC1a.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ASIC1a homomeric channels activate at pH values much closer to neutral pH compared with ASIC2a homomeric channels. The high affinity proton sensitivity of ASIC1a plays a prominent role in acidosisinduced neuronal death, and modulators that alter the pH dose response of ASIC1a affect neuronal sensitivity to prolonged acidosis (8,9,15). For example, the neuroprotective venom peptide PcTx1 increases the proton sensitivity of the ASIC1a channel, allowing the channel to desensitize at neutral pH and become unresponsive to subsequent acidic shifts in pH (16,17).…”
mentioning
confidence: 99%
“…This hypothesis is reinforced by the finding that usual therapeutic plasma concentrations of amitriptyline do not exceed 1 μM, 65 while the K D for inhibition of tetrodotoxin-sensitive Na + channels in rat dorsal root ganglia neurons is 4.7 μM. A consequence of the activatory effects of tricyclic antidepressants on ASIC1a channels, which have been shown to contribute to ischemia-related neuronal damage [20][21][22][23][24][25] is represented by changes in current therapy guidelines between long openings and adjacent brief closures) and decreased the proportion of mode 2 (association between brief openings and adjacent long closures).…”
Section: Resultsmentioning
confidence: 99%
“…17 ASIC-mediated cell Ca 2+ entry was correlated with a sustained proton-activated current component 8,9,18,19 and assumed to account for neurodegeneration consequent to ASIC activation in ischemic conditions. [20][21][22][23][24][25] Moreover, we have shown that ASIC1a Ca 2+ permeability is decreased by extracellular proteases, 26 presumably due to direct action at a cleavage site located in the extracellular loop of the channel. 27,28 Accurate single-channel recordings have reveled a wealth of details concerning the gating of ASICs: the existence of distinct gating modes and subconductance states, 29 stepwise activation by protonation of residues involved in Ca 2+ binding, 30 a long-lived desensitized state triggered by proton inflow.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ASIC functions are reported to be regulated by intracellular pH [90] . These results indicate that intracellular protons can function as modulators.…”
Section: Acid-sensing Receptors In Sensory System Sour Tastementioning
confidence: 99%